Labour Migration: Issues of Cooperation With International Organizations and Improvement of National Legislation (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article analyzes the processes of interaction of international organizations in the legal regulation of labor migration on the basis of an interdisciplinary approach. Taking into account the rights and interests of citizens of the Republic of Uzbekistan, the measures taken by our state in the following years to ensure an effective system of external labor migration were analyzed in the framework of such serious issues as the rights of labor migrants from Uzbekistan, working conditions, and lifestyle.